Freeze-thaw system for thermostable β-Galactosidase isolation from Gedong Songo Geobacillus sp. isolate - Ken Ima Damayanti; Nies Suci Mulyani; Agustina L. N. Aminin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
The effective isolation of intracellular enzymes from thermophilic bacteria is challenging because of their sturdy membrane. On the other hand, the low-cost and nontoxic method is essential for industrial food enzymes. The freeze-thaw cycles using acetone-dry ice as a frozen system was studied for efficient isolation of thermostable b-galactosidase from Geobacillus sp. dYTae-14. This enzyme has been known for application in the dairy industry to reduce the lactose content. In this study, the freeze-thaw method was performed with cycle variations 3, 5, and 7 cycles. Acetone-dry ice (-78°C) is used as a frozen system and boiling water for thawing. The b-galactosidase activity was assayed using ortho-Nitrophenyl-β-galactoside (ONPG) as substrate and protein content determined with the Lowry method. The results show that the most effective freeze-thaw is five cycles. The enzyme’s highest specific activity is 3610.13 units/mg proteins at 40-60 % ammonium sulfate saturation, with a purity value of 2.52.